Visualization tool for taxi usage analysis: A case study of lisbon, Portugal - Postsavee Prommaharaj (2018)
© 2016 ACM. This paper presents a visualization tool for taxi usage analysis. Data of taxi usage from Lisbon, Portugal is used as a case study. The tool operates on two modes; Mobility and Flow. Mobility mode displays an animation of taxi movement in the city with pick-up drop-off locations, as well as statistical information about the number of total trips made, current and recent available/occupied number of taxis, and top performance taxis. Mobility mode also allows the user to select any particular taxi to be displayed individually through a drop-down menu and search bar. Flow mode gives an overview of taxi movement with an animation of origin-destination (pick-up/drop-off) hourly flows, along with statistical graph of hourly trips made. The user can choose to view any particular time duration to observe the flow. The developed tool can be useful for taxi service providers in scheduling and dispatching management, as well as urban planning and design.